2018
DOI: 10.1159/000489695
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Basidiobolomycosis: A Case Report

Abstract: Background: Ocular basidiobolomycosis is an unusual infection caused by fungus of the order Entomophthorales. This fungus has been previously reported as a common cause of skin, subcutaneous, and gastrointestinal tract infection. The fungus isolation and its typical characteristics are clues for diagnosis of this uncommon pathogen. Case Report: A 47-year-old male patient with nodular scleritis in the left eye after an eye injury from sawdust was treated as bacterial scleritis. The lesion improved with early su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The “mycobacterial membrane protein large transporter” domain is well represented in all three subphyla of Mucoromycota as well as Basidiobolus ( fig. 2 e ) consistent with the observations of fungal–bacterial interactions documented in these lineages ( Uehling et al 2017 ; Desirò et al 2018 ; Chang et al 2019 ; Bonfante and Venice 2020 ; Tabima et al 2020 ). Although the TLD domain is universally present in almost all fungal lineages (except Wallemia ichthyophaga ), the exceptionally large number of TLD domains identified in Glomeromycotina members is unusual ( fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The “mycobacterial membrane protein large transporter” domain is well represented in all three subphyla of Mucoromycota as well as Basidiobolus ( fig. 2 e ) consistent with the observations of fungal–bacterial interactions documented in these lineages ( Uehling et al 2017 ; Desirò et al 2018 ; Chang et al 2019 ; Bonfante and Venice 2020 ; Tabima et al 2020 ). Although the TLD domain is universally present in almost all fungal lineages (except Wallemia ichthyophaga ), the exceptionally large number of TLD domains identified in Glomeromycotina members is unusual ( fig.…”
Section: Discussionsupporting
confidence: 87%
“…S1, Supplementary Material online). The complex mixed history observed in the genomes of Basidiobolus is evidenced by their enriched secondary metabolite genes many of which are result of horizontal gene transfer from Bacteria, regionally duplicated genomes, and the broad range of animal hosts it can be found to inhabit including insects, amphibians, reptiles, and human beings ( Henk and Fisher 2012 ; Tabima et al 2020 ). This may explain the sources of phylogenetic conundrums that we have encountered in the last decades using different molecular markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5,11 Several reports have described atypical cases featuring a painfree presentation, normal visual acuity, lack of corneal infiltrates, normal intraocular pressure, and absence of anterior chamber reaction. 8,[45][46][47][48] Other uncommon manifestations include aqueous fistula formation in pneumococcal scleritis, inverse hypopyon in a case of pyomyositis with S. aureus scleritis, and spontaneous IS in immunocompromised patients with no history of ocular surgery or trauma. 5,32,49 Infectious scleritis may also masquerade as other diseases, including SINS, autoimmune scleritis, ocular tumors, orbital cellulitis, cavernous sinus thrombosis, and carotidcavernous fistula.…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…Basidiobolus can be isolated from various types of environments, including soils or leaf litters, dung of frogs or lizards, and various insects (e.g., mosquitoes, mites, springtails) (Lyon et al 2001; Garros et al 2008; Manning and Callaghan 2008; Werner et al 2012). Recently, people also found that Basidiobolus can infect human eyes (Tananuvat et al 2018; Vilela and Mendoza 2018). The two CotH copies identified in Basidiobolus genomes may be involved in the pathogenic processes.…”
Section: Discussionmentioning
confidence: 99%